Acceptability of contact management and care of simple cases of COVID-19 at home: a cross-sectional study in Senegal. (12th October 2022) - Ba, Mouhamadou Faly; Ridde, Valéry; Diallo, Amadou Ibra; Tine, Jean Augustin Diégane; Kane, Babacar; Gaye, Ibrahima; Traoré, Zoumana; Bonnet, Emmanuel; Faye, Adama
Abstract: Background: COVID-19 is a major public health problem. In mid-2020, due to the health system challenges from increased COVID-19 cases, the Ministry of Health and Social Action in Senegal opted for contact management and care of simple cases at home. The objective of the study was to determine the acceptability of contact and simple case management of COVID-19 at home and its associated factors in Senegal. Methods: This was a descriptive and analytical cross-sectional study. We collected data from 11 June to 10 July 2020. We used a marginal quota sampling strategy. A total of 813 individuals took part in the survey. We collected data using a telephone interview. Results: The care of simple cases of COVID-19 at home was well accepted (78.5%). The use of home contact management was less accepted (51.4%). Knowledge of the modes of transmission of the virus and confidence in institutional information were associated with the acceptability of home care for simple cases. Regularly searching for information on COVID-19 and confidence in the government's control of the epidemic were associated with the acceptability of managing contacts at home. Conclusions: Authorities should take these factors into account for better communication to improve the acceptability and confidence in home-based care for COVID-19 and future epidemics.